A Rapid Base Assessment of Factors Influencing Corporate Crisis Communication - Jumoke SALAU; Kehinde OYESOMI; Faith OLANREWAJU (Communications of International Proceedings, 2021)
Purpose: study analyzed pieces of literature on the factors that influence crisis communications in an organisation. The paper accomplished this by reviewing several studies on crisis communication strategy used by various organisation during a crisis. Methodology: This paper used the 'situational crisis communication theories (SCCT) to explain and the cogent factor impacting crisis communication. The authors used desk, research, to compile data for the Analysis. The researcher Retrieved publications and papers from the database of Emerald Insight, Research gate, PubMed, and the Internet. Results: The findings of the literature reviewed indicate that communication during a crisis is affected by some amount of factors, such as crisis response strategy, organisational factors and stakeholder interests. Conclusion: The study concluded that in crisis communication, crisis response has a lot to do with strategic decision-making that reduces and settle the significance of the crisis on the organization and stakeholders to induce logical information that aid a corporation survive its crisis difficulties.
Keywords: Crisis; Crisis Communication; Organisation Reputation; Stakeholders